Trace multi-element doped medical nickel-titanium alloy tube and preparation method thereof

By adding trace multi-elements to medical nickel-titanium alloys and optimizing the preparation process, the technical limitations of existing medical nickel-titanium alloy tubes in terms of mechanical properties and biocompatibility are solved, and the effects of high strength, good toughness and excellent antibacteriality are achieved, providing medical devices with better material choices.

CN119710365APending Publication Date: 2025-03-28YANGTZE RIVER DELTA PHYSICS RES CENT CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411920863.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing medical nickel-titanium alloy tubes have technical limitations in terms of mechanical properties, biocompatibility and emerging application needs, making it difficult to take into account strength and toughness, and the preparation method does not control the microstructure of the material, resulting in significant performance differences.

Method used

By adding trace multi-elements, including Zn, Sn, Ge, B, Se, Zr, Cu and Ag, to the nickel-titanium alloy, to improve biocompatibility, fatigue resistance, toughening, antioxidant and antibacterial properties, and to optimize the microstructure of the material by precisely controlling the proportion of components and preparation processes.

Benefits of technology

The mechanical properties and biocompatibility of nickel-titanium alloy tubes have been significantly improved, and medical nickel-titanium alloy tubes with high strength, good toughness, excellent antibacterial properties and shape memory are obtained, providing ideal materials for the fields of vascular stents and orthopedic implants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710365A_ABST
    Figure CN119710365A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of medical nickel-titanium materials, in particular to a trace multi-element doped medical nickel-titanium alloy tube and a preparation method thereof.The trace multi-element doped medical nickel-titanium alloy tube comprises a nickel-titanium alloy tube body, and the nickel-titanium alloy tube body comprises 54.5 wt%-57.0 wt% of Ni, 42.8 wt%-45.3 wt% of Ti, an element for improving biocompatibility and fatigue resistance, a reinforcing and toughening element, an antioxidant element and an antibacterial element; the preparation method comprises the following steps: pretreating metal particles, accurately weighing, uniformly mixing, smelting and annealing to obtain a nickel-titanium tube blank; performing linear cutting to form an inner hole; the nickel-titanium tube blank is processed to the outer diameter of 4-6 mm through hot rolling and first-stage intermediate annealing, and then the nickel-titanium tube blank is processed to the outer diameter of 0.17-0.32 mm through cold drawing and second-stage intermediate annealing; and performing heat treatment and surface treatment. The obtained product has good mechanical properties and biocompatibility, the preparation method provided by the invention can control the microstructure of the product, and the product performance difference is small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical nickel-titanium materials, in particular to a medical nickel-titanium alloy tube doped with trace amounts of multiple elements and a preparation method thereof. Background Art

[0002] Nickel-titanium alloy is a typical functional material with unique shape memory effect and superelasticity, as well as certain biocompatibility, corrosion resistance and wear resistance. Therefore, it is widely used in the biomedical field, especially in applications such as vascular stents and orthopedic implants.

[0003] The composition and proportion of medical nickel-titanium alloy tubes directly affect their properties such as memory effect, mechanical properties, biocompatibility, corrosion resistance, etc. These properties are crucial to the safety and effectiveness of medical devices. Existing medical nickel-titanium alloy tubes are mainly composed of two elements, nickel and titanium. In addition, there are trace amounts of other elements, such as niobium and zirconium. The addition of these trace elements can further improve the performance of nickel-titanium alloys. However, limited by the types and proportions of the added trace elements, the performance of current medical nickel-titanium alloy tubes has considerable room for improvement, especially: (1) Mechanical properties: Existing medical nickel-titanium alloy tubes are difficult to achieve a rational balance between strength and plasticity. For example, in the application of vascular stents, they need to have sufficient strength to provide long-term support, and they also need to have good plasticity and fatigue resistance to adapt to the dynamic changes of blood vessels. For example, in the application of orthopedic implants, they need to maintain long-term stability while bearing complex mechanical loads. Existing medical nickel-titanium alloy tubes are difficult to balance strength and toughness. (2) Biocompatibility: A passivation film composed of carbon dioxide is easily formed on the surface of nickel-titanium alloy. The presence of this film can protect the nickel-titanium alloy tube from corrosion by body fluids or biological tissues, while reducing the release of nickel ions with potential biotoxicity. However, in a complex body fluid environment, the passivation film may be damaged by mechanical damage or chemical corrosion, resulting in exposure of the metal layer, which in turn causes biocompatibility issues such as local inflammation, allergic reactions, and even cytotoxicity. In addition, with the development of medical devices towards intelligence, miniaturization, and adaptability to extreme environments, existing nickel-titanium alloy tubes also show technical limitations and cannot meet the requirements of high-precision controllable deformation, reliability in extreme environments, and low magnetism.

[0004] In addition, the existing preparation methods of nickel-titanium alloy tubes do not have good control over the uniformity and stability of the material's microstructure, resulting in uneven grain size and crystal phase distribution, thus affecting the material's shape memory effect and mechanical properties, resulting in significant differences in performance between different batches of products and the inability to achieve good quality control.

[0005] To this end, this application is filed. Summary of the invention

[0006] In view of the multiple technical limitations of existing medical nickel-titanium alloy tubes in terms of mechanical properties, biocompatibility, emerging application needs, etc., and the defect that the existing preparation method of medical nickel-titanium alloy tubes has poor control over their microstructure resulting in differences in their performance, the present invention provides a medical nickel-titanium alloy tube doped with trace multiple elements and a preparation method thereof.

[0007] The present invention is achieved in that:

[0008] On the one hand, the present invention provides a medical nickel-titanium alloy tube doped with trace amounts of multiple elements, comprising a nickel-titanium alloy tube body, wherein the nickel-titanium alloy tube body comprises 54.5wt%-57.0wt% Ni and 42.8wt%-45.3wt% Ti, and the rest are other elements doped in trace amounts;

[0009] The other elements include: elements for improving biocompatibility and fatigue resistance, strengthening and toughening elements, antioxidant elements and antibacterial elements. The elements for improving biocompatibility and fatigue resistance contain Zn and Sn, the strengthening and toughening elements contain at least one of Ge and B, the antioxidant elements contain Se and Zr, and the antibacterial elements contain at least one of Cu and Ag.

[0010] Zn (zinc), on the one hand, can reduce the toxic effects of nickel-titanium alloy materials on human cells to ensure their long-term safety in the human body and improve biocompatibility. On the other hand, it can improve the fatigue resistance of nickel-titanium alloy materials and enhance the durability of nickel-titanium alloy materials under repeated stress conditions, thereby ensuring their good durability. Sn (tin) not only helps to optimize the organizational structure of nickel-titanium alloy materials, making their internal crystal structure more uniform and stable, thereby improving fatigue resistance and reducing the risk of material failure due to fatigue accumulation, but also has a positive effect on biocompatibility, which can reduce the adverse effects of nickel-titanium alloy materials on human tissues and further improve biocompatibility. The combination of Zn and Sn, their mutual influence and synergistic effect help nickel-titanium alloy materials better meet the application requirements in the biomedical field.

[0011] Ge (germanium) has a significant strengthening and toughening effect on nickel-titanium alloy materials, which can make nickel-titanium alloy materials have a certain flexibility while maintaining a high load-bearing capacity. In addition, Ge can also promote the attachment and growth of cells on the surface of nickel-titanium alloy materials, which helps the healing and integration of tissues, which is of great significance for the use of nickel-titanium alloy materials in the field of implants. B (boron) has the effect of refining grains. After grain refinement, the strength and hardness of nickel-titanium alloy materials can be significantly improved, which helps to enhance its ability to resist deformation. Moreover, the addition of B can also improve the processing properties of nickel-titanium alloy materials, making them easier to form and process during the manufacturing process, and helping to produce nickel-titanium alloy tube bodies with precise dimensions and complex shapes. Adding either Ge or B can play a role in strengthening and toughening, and improve the mechanical properties of the nickel-titanium alloy tube body.

[0012] Se (selenium) can effectively resist oxidative stress and reduce the damage caused by free radicals to nickel-titanium alloy materials, thereby extending the service life. In addition, Se also has the effect of improving the fatigue life of nickel-titanium alloy materials, so that they can better withstand repeated stress loading in the dynamic environment of the human body and meet the use requirements of complex medical environments. Zr (zirconium) not only has a significant effect on enhancing the oxidation resistance of nickel-titanium alloy materials, but also stabilizes the phase structure of nickel-titanium alloy materials, ensuring that they can maintain stable performance under different temperature and stress environments. The combination of Se and Zr, the mutual influence and synergistic effect help to significantly improve the antioxidant effect of nickel-titanium alloy materials, so that they can be used long-term and reliably in the complex and changeable human body, and further improve the biocompatibility of the nickel-titanium alloy tube body.

[0013] Cu (copper) can optimize the antibacterial properties of nickel-titanium alloy materials, effectively inhibit the growth and reproduction of bacteria on the surface of nickel-titanium alloy materials, and reduce the risk of implant infection. In addition, Cu can further improve the toughness and corrosion resistance of nickel-titanium alloy materials, so that the alloy exhibits better comprehensive performance when facing mechanical stress and chemical corrosion. Ag (silver) can effectively inhibit and kill a variety of bacteria, significantly reducing the incidence of implant-related infections. At the same time, Ag works together with other elements such as Zn to synergistically optimize other properties of nickel-titanium alloy materials such as strength, toughness, and biocompatibility, so that nickel-titanium alloy materials have higher comprehensive performance and better meet the high performance requirements of nickel-titanium alloy materials in the medical field. The addition of either Cu or Ag can have a more obvious antibacterial effect and further improve the biocompatibility of the nickel-titanium alloy tube body.

[0014] Based on traditional nickel-titanium alloy materials, the present invention significantly improves the mechanical properties and biocompatibility of the nickel-titanium alloy tube body by adding specific types of trace elements in appropriate proportions, and ultimately obtains a medical nickel-titanium alloy tube body with high strength, good toughness, excellent antibacterial properties and shape memory, which provides an ideal material for the fields of vascular stents, orthopedic implants, etc., and helps to promote the development of the medical device field towards high quality, high efficiency and high safety.

[0015] Preferably, based on the previous technical solution, the present invention has confirmed through several experiments that within the following doping amount range, each doping element and their mutual interaction can play a better role: the element for improving biocompatibility and fatigue resistance contains Zn 0.04wt%-0.09wt% and Sn 0.02wt%-0.05wt%, the reinforcing and toughening element contains Ge 0.02wt%-0.05wt% and B 0.01wt%-0.03wt%, the antioxidant element contains Se 0.05wt%-0.1wt% and Zr 0.03wt%-0.06wt%, and the antibacterial element contains Cu 0.04wt%-0.07wt% and Ag 0.01wt%-0.04wt%.

[0016] Preferably, the content ratio of Sn to Zn is 0.4-0.8, for example, it can be 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, etc.; the total content of Ge and B is 0.02wt%-0.06wt%, for example, it can be 0.02wt%, 0.025wt%, 0.03wt%, 0.035wt%, 0.04wt%, 0.045wt%, 0.05wt%, 0.055wt%, 0.06wt%, etc. ; The content ratio of Zr to Se is 0.3-0.6, for example, it can be 0.3, 0.35, 0.4, 0.45, 0.50, 0.55, 0.6, etc.; The total content of Cu and Ag is 0.06wt%-0.09wt%, for example, it can be 0.06wt%, 0.062wt%, 0.064wt%, 0.066wt%, 0.068wt%, 0.07wt%, 0.075wt%, 0.08wt%, 0.085wt%, 0.09wt%, etc.

[0017] The ratio of Sn to Zn is controlled at 0.4-0.8. In this ratio range, the synergistic effect of Sn and Zn is most obvious, which can significantly optimize the oxidation resistance and fatigue resistance of nickel-titanium alloy materials. Good oxidation resistance enables nickel-titanium alloy materials to effectively resist the damage caused by the oxidative environment inside and outside the body, avoid the degradation of material performance due to oxidation reactions, and thus reliably extend their service life in biomedical applications; good fatigue resistance enables nickel-titanium alloy materials to better maintain the stability of their own structure and performance in the complex dynamic environment of the human body, and reduce the risk of material failure caused by fatigue accumulation. More importantly, the appropriate Sn / Zn ratio helps promote the attachment and growth of cells on the surface of nickel-titanium alloy materials, which is extremely critical for medical devices implanted in the human body. It can promote good integration between implants and human tissues and comprehensively enhance the ability of nickel-titanium alloy materials to meet the needs of biomedical applications.

[0018] The total content of Ge and B is controlled at 0.02wt%-0.06wt%. Within this range, the combination and synergy of Ge and B help to achieve an ideal balance between antibacterial properties, biocompatibility and fatigue resistance. Ge can not only enhance the strength and toughness of nickel-titanium alloy materials, but also help cells to attach and grow on the surface of nickel-titanium alloy materials at the cellular level, thereby optimizing their biological properties; the addition of B can refine the grains of nickel-titanium alloy materials, thereby improving the strength and hardness of the alloy and improving its processing properties. Although the addition of Ge or B can enhance toughness, the effect of adding them together is better. When the two elements are added together, on the one hand, the effect of B in refining the grains and the effect of Ge in promoting cell attachment and growth can further enhance biocompatibility, ensure that the nickel-titanium alloy materials can get along with human cells after being implanted in the human body, and ensure safety of use; on the other hand, the two elements jointly help to improve the fatigue resistance of nickel-titanium alloy materials and improve the mechanical properties of nickel-titanium alloy materials, so that nickel-titanium alloy materials can still maintain good durability during long-term use under alternating stress.

[0019] The content ratio of Zr to Se is controlled at 0.3-0.6. This content ratio plays an important role in constructing a stable grain structure of nickel-titanium alloy materials. The addition of Zr can stabilize the phase structure of nickel-titanium alloy materials, and synergistically with B to promote the formation of a finer and more uniform grain morphology of nickel-titanium alloy materials. This grain morphology can directly improve the strength and hardness of the material, enhance the ability of nickel-titanium alloy materials to resist deformation, and enable them to maintain good performance under different stress conditions. Se can effectively resist oxidative stress and reduce the damage caused by free radicals to nickel-titanium alloy materials. Zr and Se are used in combination, which influence and synergize each other. On the one hand, the stability and reliability of long-term use of nickel-titanium alloy materials are improved from the perspective of their microstructure, and on the other hand, their ability to resist oxidation is improved from the perspective of material composition. Under the combined effect, nickel-titanium alloy materials can be used long-term and reliably in the complex and changeable human body, further improving the biocompatibility of the nickel-titanium alloy tube body.

[0020] The total content of Cu and Ag is controlled at 0.06wt%-0.09wt%. This content range helps to maximize the synergistic effect of Cu and Ag. The antibacterial properties of Cu and Ag are complementary, which further enriches and enhances the antibacterial properties of the nickel-titanium alloy material. At the same time, the combined effect of Cu, Ag and Zn can enhance the toughness, fatigue resistance and corrosion resistance of the alloy, further improving the performance of the nickel-titanium alloy tube body.

[0021] Preferably, based on the previous scheme, the present invention unexpectedly found that when the total content of B and Zr is 0.05-0.08 and the content ratio of B to Zr is 0.3-0.6, the strength, stability and deformation capacity of the nickel-titanium alloy material are optimal. It is speculated that within this content range, B and Zr have a good synergistic effect, jointly promoting grain refinement and maintaining its stable existence and uniform distribution, thereby effectively balancing strength and toughness, so that the nickel-titanium alloy material has excellent mechanical properties.

[0022] Furthermore, the present invention found that when the doping elements in a certain nickel-titanium alloy material simultaneously satisfy the above-mentioned proportional relationship, its phase transition temperature range is 30-33°C. This relative temperature allows the nickel-titanium alloy material to always maintain stable performance within the range of human physiological temperature changes. For example, vascular stents can accurately maintain their shape memory effect and superelasticity when the human body temperature fluctuates, provide reliable support for blood vessels, and adapt to the dynamic physiological movement of blood vessels, effectively preventing problems such as stent displacement or failure. It is speculated that the possible mechanism should be: at room temperature, nickel-titanium alloy mainly presents a martensite phase. This phase structure gives the alloy good plastic deformation ability, which is convenient for cold working operations such as cold drawing and cutting, and is conducive to the manufacture of medical device components with complex shapes. When the temperature rises to above 37°C, the alloy transforms into an austenite phase, which has a high elastic modulus and excellent shape recovery ability, and can adapt well to the human body temperature environment. Under this ratio condition, the appropriate amount of Se changes the electronic structure and atomic interaction of the nickel-titanium alloy, affecting the thermodynamic process of phase transition; the appropriate amount of Ge element forms a solid solution with the nickel-titanium matrix, changing the lattice parameters and phase stability, and the phase transition temperature is adjusted under the synergistic effect of Se and Ge.

[0023] Preferably, it further comprises a drug release coating disposed on the surface of the nickel-titanium alloy tube body, wherein the drug release layer contains PLGA loaded with antibacterial drugs and / or anti-inflammatory drugs.

[0024] By setting a drug release coating on the surface of the nickel-titanium alloy tube body, antibacterial drugs and / or anti-inflammatory drugs can be accurately loaded on PLGA and then released on demand. The setting of the drug release layer not only helps to reduce the infection risk of the implant, but also provides support for anti-infection treatment, which helps to explore the application potential of medical nickel-titanium alloy tubes in the field of therapeutic medical devices.

[0025] Compared with the prior art, the medical nickel-titanium alloy tube doped with trace amounts of multiple elements proposed in the present invention has the following beneficial effects:

[0026] (1) Strong mechanical properties

[0027] By adding specific types of trace elements in appropriate proportions, especially accurately controlling the addition of basic elements such as Ni and Ti and strengthening and toughening elements such as Ge and B, the tensile strength of the nickel-titanium alloy tube body obtained by the present invention can reach 800-1000MPa, and the yield strength exceeds 600MPa; after the drug release coating is set on its surface, the tensile strength and yield strength can be further significantly improved. Excellent mechanical properties help to improve the stability and reliability of nickel-titanium alloy tubes in long-term use.

[0028] (2) Good biocompatibility

[0029] By adding specific types of trace elements in appropriate proportions, especially by reasonably setting the Ni content range and precisely controlling the addition of Sn, Zn and other elements that improve biocompatibility and fatigue resistance, the nickel-titanium alloy tube body obtained by the present invention significantly reduces the amount of nickel ion precipitation when used in human tissue. The nickel release amount is 0.25-0.5μg·cm after simulated body fluid immersion experiment. -2 ·week -1 (micrograms per square centimeter per week), which is much lower than the nickel release standard set by the European Standards Committee (EN 1811:2023 requires the nickel release result of medical devices to be ≤0.88μg·cm -2 ·week -1 ). In addition, it has significant antibacterial properties and good inhibitory effects on common bacteria; it helps cell attachment, effectively promotes tissue healing and integration, and allows for better integration between implants and human tissues. Good biocompatibility effectively reduces the harm to the human body caused by long-term contact between the medical nickel-titanium alloy tube body and human tissues, greatly improving its application safety in the biomedical field.

[0030] (3) Has certain therapeutic functions

[0031] With the help of the drug release layer arranged on its surface, antibacterial drugs and / or anti-inflammatory drugs can be accurately loaded on PLGA, so that the nickel-titanium alloy tube has the function of releasing antibacterial and / or anti-inflammatory drugs, which not only helps to reduce the infection risk of implants, but also provides support for anti-infection treatment, and helps to explore the application potential of medical nickel-titanium alloy tubes in the field of therapeutic medical devices.

[0032] (4) Excellent overall performance

[0033] In addition to mechanical properties and biocompatibility, other properties such as shape memory, fatigue resistance, corrosion resistance, and surface quality are also excellent. Therefore, the medical nickel-titanium alloy tube proposed in the present invention has broad application prospects and is expected to provide better material options for medical devices such as vascular stents and orthopedic implants, which will help promote the development of medical devices towards safer, more efficient, and more functional directions.

[0034] On the other hand, the present invention provides a method for preparing a medical nickel-titanium alloy tube doped with trace amounts of multiple elements, wherein the method for preparing the nickel-titanium alloy tube body comprises the following steps:

[0035] S1, preparing metal particles corresponding to the composition of the nickel-titanium alloy tube body, accurately weighing them after pretreatment, and then mixing them evenly and melting and annealing them to obtain a nickel-titanium rod blank;

[0036] S2, after the initial processing of the nickel-titanium rod blank, turning it into a nickel-titanium tube blank with an outer diameter of 20-30 mm, and then forming an inner hole with a diameter of 7-9 mm in the middle of the nickel-titanium tube blank by wire cutting;

[0037] S3, firstly perform hot rolling and primary intermediate annealing treatment in a cycle to process the nickel-titanium tube blank obtained in the previous step to an outer diameter of 4-6 mm, and then perform cold drawing and secondary intermediate annealing treatment in a cycle until the outer diameter is 0.17-0.32 mm;

[0038] S4. After heat treatment and surface treatment, the finished product is obtained.

[0039] It should be noted that:

[0040] In S2, the specific operation of wire cutting is: firstly, a hole for the cutting wire to be inserted is formed in the middle of the nickel-titanium tube blank by electric spark drilling, and then the cutting wire is inserted to cut the inner hole by wire cutting; preferably, the obtained product is electrolytically processed after wire cutting to improve the surface properties;

[0041] In S4, the heat treatment is mainly to avoid grain growth or performance degradation, promote the formation and uniform distribution of precipitation phase, and further improve the strength and shape memory properties. It is preferably treated at 550-650°C for 1-10min; the surface treatment mainly includes cleaning treatment, such as cleaning with supercritical carbon dioxide. The preferred cleaning conditions are: 50-55°C, 9-10MPa, flow rate 0.5-1.0L / min, cleaning 20-30min, to remove pollutants and improve the surface cleanliness and flatness of the product.

[0042] Preferably, in step S1, the weighing errors of Ni and Ti are controlled within ±0.02wt% during weighing, the purity of other elements is ≥99.99% and the weighing error is controlled within ±0.003wt%; the pretreatment of the metal particles at least includes: cleaning the Ni particles to remove the surface oil and oxide layer and drying, cleaning the Ti particles to remove the surface oil and drying, and heat treating the Ni particles, Ti particles and other element particles respectively, and accurately weighing the Ni particles, Ti particles and other element particles after pretreatment and mixing them evenly; in step S1, the smelting adopts a combination of vacuum induction melting and electron beam melting, and after the smelting is completed, it is first cooled to 900-1000℃ at a rate of 20-30℃ / min, and then cooled to room temperature at a rate of 5-10℃ / min.

[0043] In this embodiment, when preparing the corresponding metal particles, it is preferred to use metal particles with uniform particle size and shape to ensure uniform mixing and prevent uneven distribution of elements during smelting, which in turn has an adverse effect on the performance of the nickel-titanium alloy material.

[0044] In this embodiment, plasma cleaning technology is used to clean the surface of Ni particles. The preferred cleaning conditions are: power 50-200W, processing time 10-30min, so as to remove oil and oxide layer on the surface of Ni particles. After cleaning, rinse to neutral and dry.

[0045] In this embodiment, laser cleaning technology is preferably used to clean the surface of the Ti particles to remove oil stains on the surface of the Ti particles, and the Ti particles are rinsed to neutral and dried after cleaning.

[0046] In this embodiment, the heat treatment is to heat the metal particles under the protection of an inert gas to remove surface oxides and improve the reactivity during smelting. For example, the heat treatment method of Ti particles can be: placing the Ti particles in a deoxidation furnace, passing argon gas with an argon flow rate of 5-10L / min, and treating at 500-700°C for 30-60min; for another example, the heat treatment method of Ni particles can be: placing the Ni particles in a deoxidation furnace, under the protection of argon gas with a purity of not less than 99.9%, and treating at 300-400°C for 20-40min. Other trace doped element particles are also similarly operated.

[0047] In this embodiment, in order to ensure that various metal particles are mixed uniformly, various metal particles that have been pretreated and accurately weighed are put into a three-dimensional mixer together and mixed at a rotation speed of 10-30 rpm for 30-60 minutes to prepare for smelting.

[0048] In this embodiment, strict and accurate weighing error control and purity requirements can ensure the accurate proportion of the main materials Ni, Ti and various alloy elements doped in trace amounts, laying the foundation for the excellent performance of the nickel-titanium alloy material. In addition, the high purity requirement can also ensure low impurity content, avoid adverse effects on the performance of the nickel-titanium alloy material due to impurities, and ensure the reliability of product quality.

[0049] The above steps work together to help achieve the purpose of accurate material preparation. Accurate mixing of various metal elements according to the designed proportions is the basic prerequisite for obtaining nickel-titanium alloy materials with good comprehensive performance.

[0050] On the basis of precise batching, vacuum induction melting and electron beam melting are combined for melting. Vacuum induction melting uses a vacuum induction melting furnace, which is first evacuated to a vacuum degree of ≤5×10 -4Pa, then raise the temperature to 1500-1600℃ at a heating rate of 50℃ / min and keep it warm for 15min, repeat the melting 2-4 times to ensure sufficient melting and uniform composition. Turn on electromagnetic stirring during the melting process to make the melt composition uniform. After the vacuum induction melting is completed, a graded cooling strategy is adopted: first cool to 900-1000℃ at a faster rate of 20-30℃ / min, and then cool to room temperature at a slower rate of 5-10℃ / min. This graded cooling method helps to form uniform and fine grains, and synergizes with trace doping elements Zr and B to promote grain refinement and inhibit grain growth, playing a key role in regulating the microstructure and properties of the alloy. Then, electron beam melting is carried out. Electron beam melting uses an electron beam melting furnace equipped with a multi-source electron gun, which is first evacuated to a vacuum degree of ≤1×10 -5 Pa, then the temperature is raised to 1750-1850℃ at a heating rate of 100℃ / min, and the melting is repeated 3-5 times, with a cooling interval of 30 minutes after each remelting. The combination of vacuum induction melting and electron beam melting not only helps to complement each other's advantages, improve melting efficiency and quality, and meet the high requirements of the melting process for multi-element alloys, but also helps to disperse and evenly distribute various trace doping elements, so that they have a strong interface bonding force with the main material Ni and Ti matrix, so as to effectively hinder dislocation movement and improve the strength of nickel-titanium alloy materials.

[0051] In order to further optimize the microstructure, on this basis, after the heat treatment in step S4, a graded cooling method is also preferably adopted, such as first cooling to 200-300°C at a cooling rate of 20°C / min, and then cooling to room temperature at a cooling rate of no more than 10°C / min, so as to further optimize the microstructure and reduce internal stress.

[0052] Preferably, in step S3, the conditions for hot rolling and primary intermediate annealing are as follows: hot rolling temperature is 850-950°C, reduction is 30%-50%, primary intermediate annealing temperature is 600-700°C, time is 10-50min and is carried out under inert gas protection.

[0053] In this embodiment, hot rolling is performed at 850-950° C., and the reduction is set to 30%-50%. During the hot rolling process, the grains undergo dynamic recrystallization during the deformation process, thereby achieving grain refinement, optimizing the grain structure, and improving the strength and toughness of the alloy.

[0054] In this embodiment, the first-stage intermediate annealing after hot rolling is performed under the protection of high-purity argon (oxygen content ≤ 10ppm). During the first-stage intermediate annealing, the internal structure of the grains is adjusted by atomic diffusion, and residual stress is eliminated, which helps to further stabilize the grain size and distribution, ensure that the alloy has good strength, stability and deformation ability, and effectively balance strength and toughness.

[0055] In this embodiment, the thermomechanical treatment process combining hot rolling and primary intermediate annealing works synergistically and influences each other, and further optimizes the microstructure of the nickel-titanium alloy material on the basis of graded cooling to refine the grains. The resulting grain structure provides excellent mechanical properties for the nickel-titanium alloy material in medical device applications.

[0056] It should be noted that in step S3, cold drawing and secondary intermediate annealing are conventional technical means, the purpose of which is to further process the hot-rolled product to obtain the required size of the finished medical capillary nickel-titanium tube: outer diameter 0.2-0.4mm, wall thickness 0.03-0.05mm. For example, it can be carried out according to the following process: the first compression rate is 10%-25%, the drawing amount is about 10%, no online power heating, the total compression rate between the two intermediate annealings is 35%-45%, the drawing speed is 5-10m / min, and the mandrel is drawn. The material of the mandrel is consistent with that of the nickel-titanium tube. When the outer diameter is drawn to 0.2-0.4mm, it is heated at 200-300℃ for 5-10min, and the mandrel is pulled out at both ends at the same time. The secondary intermediate annealing treatment can be carried out in any of the following two ways: Method 1: online induction annealing, induction coil heating device, current frequency 5-50kHz, power 5-50kW, heating to 350-600℃, 3-8L / min high-purity argon protection; Method 2: annealing under inert atmosphere protection, temperature 500-700℃, time 5-25min.

[0057] Preferably, the method further comprises step S5 for forming a drug-releasing coating on the surface of the finished product. Step S5 specifically comprises: firstly coating the surface of the finished product with a drug carrier layer whose active ingredient is PLGA, then immersing the finished product in a solution containing the drug, then taking it out and drying it, coating the surface with chitosan, and finally curing it.

[0058] More preferably, the specific operation of step S5 is as follows: coating the drug carrier layer: spraying or spin coating a chloroform or ethyl acetate solution containing 10wt%-15wt% PLGA and an acetic acid aqueous solution containing 0.5wt%-1wt% chitosan onto the surface of the finished product to form a 5-10μm thick PL GA-chitosan layer, and vacuum drying; the acetic acid aqueous solution is 0.5% by mass; drug embedding: firstly prepare the antibacterial drug and / or anti-inflammatory drug into an aqueous solution with a concentration of 0.5-2mg / ml or a hydroalcohol solution with a water-ethanol volume ratio of 1:1, and then immerse the finished product obtained in the previous step therein and keep it for 15-30min, and finally take it out to dry or vacuum dry; coating the control layer: firstly coat chitosan with a thickness of 1-2μm, and then dry; curing treatment: thermal curing at 50-70°C or cross-linking curing under ultraviolet light of 365nm.

[0059] In this embodiment, when coating the drug carrier layer, the spraying rate during spraying or spin coating is preferably 0.5-1 ml / min, the stirring speed is 100-300 rpm, the vacuum drying temperature is 40-50° C., and the time is 1-2 h.

[0060] In this embodiment, the antibacterial and anti-inflammatory drugs can specifically be vancomycin, dexamethasone, etc. These drugs are first dissolved in water or ethanol water with a volume ratio of 1:1 to form a solution with a concentration of 0.5-2 mg / ml, and then the finished product is immersed in it. After the immersion is completed, it is naturally dried or vacuum dried.

[0061] In this embodiment, chitosan is added to the coating drug carrier layer, which can increase the stability of the drug loaded on PLGA in the organism, and can also improve biocompatibility and enhance targeting. Chitosan is used as a coating control layer, and is designed according to the requirements of the above technical parameters. The purpose of controlling the drug release rate and release amount can be achieved by adjusting the ratio of chitosan and PLGA and the degree of cross-linking. This precise, controlled release property helps to achieve the sustained release and sustained action of the drug and improve the bioavailability of the drug.

[0062] In this embodiment, the curing time at 50-70° C. is preferably 1.5-3 h, and the cross-linking curing time under 365 nm ultraviolet light is 15-25 min.

[0063] After the above operation, a firmly attached drug release coating can be obtained on the surface of the nickel-titanium alloy tube body. The drug release coating has a stable drug release rate, which can effectively reduce the infection risk of the implant and achieve accurate drug release, broadening the application field of medical nickel-titanium alloy tubes. Moreover, the drug release coating is attached to the surface of the nickel-titanium alloy tube body and is closely combined with it, which helps to play a long-term, continuous and stable role.

[0064] Compared with the prior art, the preparation method proposed in the present invention can effectively control the microstructure of the grains by adding grain refiners B and Zr through precise control of the solidification cooling rate and the thermomechanical treatment process, and synergize with various trace multi-elements to significantly improve the strength and stability of the nickel-titanium alloy material. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0066] Figure 1 This is a SEM image of the medical nickel-titanium alloy tube obtained in Example 1;

[0067] Figure 2 This is a SEM image of the medical nickel-titanium alloy tube obtained in Example 2;

[0068] Figure 3 This is the SEM image of the medical nickel-titanium alloy tube obtained in Comparative Example 2. DETAILED DESCRIPTION

[0069] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of this application. The operations not described in detail in the following embodiments and comparative examples are all conventional technical means in this field.

[0070] The raw materials involved in the following examples and comparative examples that are not clearly stated are all conventional raw materials in the art and can be commercially obtained in the prior art. The technical operations that are not clearly stated or described in detail in the following examples and comparative examples are all conventional technical operations in the art.

[0071] The following examples and comparative examples involve some of the following operational requirements for testing: chemical composition detection using ICP-MS and XRF cross-verification to ensure data accuracy; in the corrosion resistance test, a salt spray test was used in accordance with ASTM-B117 standard, and an electrochemical corrosion test was performed in a 3.5wt% sodium chloride solution using three electrodes, and an accelerated corrosion test was performed in accordance with ASTM-G44 standard. The electrochemical impedance spectroscopy test used a 3.5wt% sodium chloride solution, and the test frequency was 10m-100kHz and the amplitude was 5mV at an open circuit potential; the adhesion test of the drug release coating specifically includes a scratch test and a peel test. The scratch test uses a Rockwell hardness tester and a diamond cone indenter with a load of 50N, and the peel test uses a 180° peel test method; hardness and elasticity The elastic modulus was tested by nanoindentation test with a Berkovich indenter, a maximum loading force of 50mN, a loading rate of 0.5mN / s, a load holding time of 10s, and an unloading rate of 0.5mN / s. The toughness was tested by a three-point bending test with a span of 20-30mm and a loading rate of 0.1-0.5mm / min. The surface performance test included surface roughness and glossiness tests. The surface roughness was tested by atomic force microscopy with a scanning area of ​​10μm×10μm, and the gloss was tested by a glossmeter with an incident angle of 60°. For the biomedical performance test, the product was placed in a simulated human body fluid environment at 37±0.5℃ and incubated for a certain period of time. The liquid was then taken and the element concentration was tested by ICP-MS. At the same time, RTCA and luciferase methods were used to measure activity and toxicity tests were conducted on multiple cell lines.

[0072] Example 1

[0073] A medical nickel-titanium alloy tube doped with trace multiple elements comprises a nickel-titanium alloy tube body and a drug-releasing coating arranged on the surface of the nickel-titanium alloy tube body, wherein the nickel-titanium alloy tube body comprises 56.155wt% Ni, 43.5wt% Ti, 0.03wt% Sn, 0.06wt% Zn, 0.035wt% Ge, 0.02wt% B, 0.04wt% Zr, 0.08wt% Se, 0.05wt% Cu and 0.03wt% Ag, and the drug-releasing layer contains PLGA loaded with vancomycin.

[0074] The preparation method of the above-mentioned trace multi-element doped medical nickel-titanium alloy tube specifically comprises the following steps:

[0075] S1, preparing metal particles corresponding to the composition of the nickel-titanium alloy tube body, accurately weighing them after pretreatment, and then mixing them evenly and melting and annealing them to obtain a nickel-titanium rod blank;

[0076] Pretreatment: Select raw materials with a purity of ≥99.99%, check the particle size, shape and distribution with the help of a microscope and a particle size analyzer to ensure uniformity and prevent uneven distribution of elements during smelting, and then carry out pretreatment; pretreatment mainly includes surface cleaning, drying and heat treatment; surface cleaning and drying are mainly for Ni particles and Ti particles. Ni particles use plasma cleaning technology with a power of 120W for 20 minutes to remove oil and oxide layers and rinse to neutrality after cleaning. Ti particles use laser cleaning technology to remove surface oil and rinse to neutrality, and then Ni particles and Ti particles are dried at 100°C for 3 hours respectively to prevent moisture from affecting the quality of the alloy; heat treatment is for all elements, that is, all elements are slightly annealed under inert gas protection to remove oxides and improve activity during smelting reactions;

[0077] Precise weighing: Prepare materials accurately according to the proportion, strictly control the error of nickel and titanium components within ±0.02wt%, and the error of other elements within ±0.003wt%, to ensure that the element content and proportion meet the standards;

[0078] Mixing: Put all the raw materials into a three-dimensional mixer, stir at 20 rpm for 45 minutes to fully mix them to avoid agglomeration, and vacuum process them after mixing;

[0079] Melting: First use a vacuum induction melting furnace with a vacuum degree of ≤5×10 -4 Pa, heating rate 50℃ / min, melting temperature 1550℃, heat preservation 15min, intermittent electromagnetic stirrer, stirring for 3min each time, remelting 4 times to optimize the uniformity of material composition; after melting, first cool to 950℃ at a rate of 25℃ / min, and then cool to room temperature at a rate of 8℃ / min to optimize the microstructure, reduce internal stress, and control phase change behavior; then electron beam melting is carried out, using an electron beam melting furnace equipped with a multi-source electron gun, and the vacuum degree is ≤1×10 -5 Pa, melting temperature 1800℃, heating rate 100℃ / min, remelting 4 times, cooling interval 30min after each remelting, to maintain thermal stability and improve quality;

[0080] Annealing: Annealing temperature 650℃, annealing time 45min, high-purity argon protection, oxygen content ≤10ppm, to prevent material oxidation;

[0081] S2, after the initial processing of the nickel-titanium rod blank, turning it into a nickel-titanium tube blank with an outer diameter of 20-30 mm, and then forming an inner hole with a diameter of 7-9 mm in the middle of the nickel-titanium tube blank by wire cutting;

[0082] Initial processing of the billet: Turning and grinding the cast billet to remove the oxide layer and shrinkage defects of the cast billet, so that the surface roughness of the billet is ≤1.6μm;

[0083] Drilling, threading, and processing inner holes: Use electric spark drilling with a current of 30A and a pulse frequency of 10kHz, then insert the cutting wire to obtain a nickel-titanium tube blank with an inner diameter of 8mm and an outer diameter of 25mm by wire cutting;

[0084] Electrolytic polishing: The active ingredients of the electrolyte are sodium citrate (concentration 0.2 mol / L), disodium hydrogen phosphate (concentration 0.1 mol / L), and boric acid (concentration 0.15 mol / L), the electrolytic current is 30 A, the electrolytic voltage is 20 V, the electrolytic time is 15 min, and the distance between the cathode and anode is 10 mm;

[0085] S3, firstly perform hot rolling and primary intermediate annealing treatment in a cycle to process the nickel-titanium tube blank obtained in the previous step to an outer diameter of 5 mm, and then perform cold drawing and secondary intermediate annealing treatment in a cycle until the outer diameter is 0.3 mm;

[0086] Hot rolling: hot rolling is carried out using a three-roll mill at a temperature of 900°C, a reduction of 40%, and a speed of 3m / min, so that the grains undergo dynamic recrystallization during the deformation process and the grains are refined;

[0087] Primary intermediate annealing treatment: temperature 650°C, time 30 min, high-purity argon protection, oxygen content ≤ 10ppm, adjust the internal structure of the grains through atomic diffusion, eliminate residual stress, and further stabilize the grain size and distribution;

[0088] Cold drawing: The first compression rate is 20%, the drawing amount is about 10%, no online power heating, the total compression rate between the two intermediate annealing is 40%, the drawing speed is 8m / min, the drawing is with a mandrel, the material of the mandrel is consistent with the nickel-titanium tube, when the outer diameter is drawn to 0.3mm, it is heated at 250℃ for 8min, and the mandrel is pulled out at both ends at the same time; the temperature of the secondary intermediate annealing treatment is 600℃, the time is 15min, and high-purity argon gas protection;

[0089] S4. After heat treatment and surface treatment, the finished product is obtained.

[0090] Heat treatment: temperature 580℃, time 3min, to avoid grain growth or performance degradation, promote the formation and uniform distribution of precipitation phase, and improve strength and shape memory performance;

[0091] Surface treatment: Cleaning and drying with supercritical carbon dioxide at a temperature of 53°C, a time of 25 minutes, a cleaning pressure of 9.5 MPa, and a supercritical carbon dioxide flow rate of 0.8 L / min to remove pollutants and improve surface cleanliness and flatness;

[0092] The nickel-titanium alloy tube body was observed through a metallographic microscope, and it was found that the grains thereof were in a uniform equiaxed crystal morphology, and the average grain size was 3-18 μm;

[0093] S5. Spray a chloroform solution containing 12 wt% PLGA and an acetic acid aqueous solvent containing 0.8 wt% chitosan onto the surface of the nickel-titanium alloy tube body to form a PLGA-chitosan layer of 8 μm thick. The spraying speed is 0.8 mL / min and the stirring speed is 200 rpm. After spraying, the tube is vacuum dried at 45°C for 1.5 h. The acetic acid aqueous solvent is an acetic acid aqueous solution with a mass percentage of 0.5%. First, prepare vancomycin into a 1 mg / ml aqueous alcohol solution (water-ethanol volume ratio of 1:1), and then immerse the nickel-titanium alloy tube body obtained in the previous step in it and keep it for 20 minutes. Finally, take it out and place it in a vacuum environment at 50°C for 1 hour. Coating the control layer: first coat 1.5 μm thick chitosan, and then dry it. Curing treatment: heat cure at 60°C for 2 hours.

[0094] The obtained medical nickel-titanium alloy tube was placed in simulated human body fluid at 37±0.5°C, and the drug release rate exceeded 80% in 48 hours.

[0095] After testing: (1) The yield strength of the medical nickel-titanium alloy tube (i.e., the surface of the nickel-titanium alloy tube body with a drug release coating) is 720MPa, the tensile strength is 1150MPa, the elongation (gauge length 50mm) is 22.5%, and there is no obvious crack or deformation after 1000 simulated physiological loading cycles. (2) The biomedical performance test shows that the nickel ion release after being placed in simulated human body fluid for 7 days is 0.2μg / L; the toxicity test on multiple cell lines such as fibroblasts and epithelial cells shows that the cell viability is 95% for 24 hours and 90% for 48 hours; osteoblasts, endothelial cells, etc. are inoculated on the surface of the product, and the cell attachment rate is 50% after 24 hours of culture, 70% after 48 hours of culture, and 85% after 72 hours of culture. (3) The antibacterial test shows that the diameter of the antibacterial zone for Escherichia coli is 20mm, and the diameter of the antibacterial zone for Staphylococcus aureus is 22mm. (4) The deformation recovery rate at 37°C is 98%, and the deformation recovery rate after 10 cycles of stretching is 97.3%. The rate of decrease in deformation recovery rate is very low. (5) The salt spray test shows that the corrosion area is ≤1% in 336h; the electrochemical corrosion test shows that its corrosion potential is -0.1V; the accelerated corrosion test shows that the corrosion area is ≤2%. (6) The scratch test shows that the peeling area is 7.5% at 55N, and the maximum peeling force of the drug release coating is 11.2N / cm. (7) The hardness is 12.5GPa, the elastic modulus is 160GPa, and the fracture strain of the three-point bending test is 2.8%. (8) The surface roughness is 0.1μm and the gloss is 90.

[0096] Example 2

[0097] Compared with Example 1, step S5 is not performed, and the rest is the same as Example 1.

[0098] After testing: (1) The yield strength of the nickel-titanium alloy tube body is 700MPa, the tensile strength is 1000MPa, and the elongation is 25%. Compared with Example 1, it can be seen that after setting the drug release coating, the yield strength and tensile strength of the product are greatly improved, and the elongation decreases slightly. (2) The antibacterial test shows that the diameter of the inhibition zone for Escherichia coli is 15mm, and the diameter of the inhibition zone for Staphylococcus aureus is 18mm. Compared with Example 1, it can be seen that the antibacterial property of the product is stronger after setting the drug vancomycin release coating. (3) The deformation recovery rate at 37°C is 95%, and the deformation recovery rate after 10 cycles of stretching is 93.8%, which is very low. Compared with Example 1, it can be seen that the deformation recovery rate is improved after setting the drug release layer, and the decrease rate of the deformation recovery rate after cyclic stretching has a more obvious downward trend, which helps to optimize the shape memory stability of the product. (4) Salt spray test shows that the corrosion area is ≤5% in 72h; the electrochemical corrosion test shows that its corrosion potential is -0.5V; the corrosion resistance is excellent. Compared with Example 1, it can be seen that the setting of a drug release layer helps to further optimize the corrosion resistance of the product. (5) The hardness is 8.6GPa, the elastic modulus is 140GPa, and the fracture strain of the three-point bending test is 2.2%, which has good hardness and toughness. Compared with Example 1, it can be seen that the setting of the drug release coating helps to further optimize the hardness and toughness. (6) The surface roughness is 0.5μm and the glossiness is 60. The surface performance is good. Comparison Figure 1 and Figure 2 It can be seen that better surface properties can be obtained after setting the drug release coating.

[0099] Example 3

[0100] Compared with Example 2, the component contents of the nickel-titanium alloy tube body are different, specifically including 55.34wt% Ni, 44.3wt% Ti, 0.02wt% Sn, 0.09wt% Zn, 0.05wt% Ge, 0.02wt% B, 0.03wt% Zr, 0.1wt% Se, 0.04wt% Cu and 0.01wt% Ag. The rest are the same as Example 2.

[0101] Example 4

[0102] Compared with Example 2, the component contents of the nickel-titanium alloy tube body are different, specifically including 54.5wt% Ni, 45.16wt% Ti, 0.02wt% Sn, 0.09wt% Zn, 0.02wt% Ge, 0.03wt% B, 0.03wt% Zr, 0.1wt% Se, 0.04wt% Cu and 0.01wt% Ag. The rest are the same as Example 2.

[0103] Example 5

[0104] Compared with Example 2, the component contents of the nickel-titanium alloy tube body are different, specifically including 56.86wt% Ni, 42.8wt% Ti, 0.05wt% Sn, 0.04wt% Zn, 0.05wt% Ge, 0.01wt% B, 0.06wt% Zr, 0.05wt% Se, 0.07wt% Cu and 0.01wt% Ag. The rest are the same as Example 2.

[0105] Example 6

[0106] Compared with Example 2, the component contents of the nickel-titanium alloy tube body are different, specifically including 55.63wt% Ni, 44.0wt% Ti, 0.04wt% Sn, 0.08wt% Zn, 0.05wt% Ge, 0.01wt% B, 0.06wt% Zr, 0.05wt% Se, 0.07wt% Cu and 0.01wt% Ag. The rest are the same as Example 2.

[0107] The same test items as in Example 2 were carried out on Examples 3 to 6, and the test results showed that each of the above examples could obtain a nickel-titanium alloy tube body that was close to the test results of Example 2, had excellent comprehensive performance, and could meet the medical use requirements. Furthermore, the relative order of advantages and disadvantages of the examples was: Example 2> Example 6> Example 5> Example 4> Example 3. Obviously, the performance of the nickel-titanium alloy tube body is closely related to the doping amount of the doping elements and the relative proportion between them.

[0108] Example 7

[0109] Compared with Example 2, the component contents of the nickel-titanium alloy tube body are different, specifically including Ni 55.611wt%, Ti 44.0wt%, Sn 0.04wt%, Zn 0.08wt%, Ge 0.05wt%, B 0.01wt%, Zr 0.04wt%, Se0.089wt%, Cu 0.07wt% and Ag 0.01wt%. The rest are the same as Example 2.

[0110] Example 8

[0111] Compared with Example 2, the component contents of the nickel-titanium alloy tube body are different, specifically including 55.599wt% Ni, 44.0wt% Ti, 0.04wt% Sn, 0.08wt% Zn, 0.05wt% Ge, 0.01wt% B, 0.05wt% Zr, 0.091wt% Se, 0.07wt% Cu and 0.01wt% Ag. The rest are the same as Example 2.

[0112] Example 9

[0113] Compared with Example 2, the component contents of the nickel-titanium alloy tube body are different, specifically including 55.61wt% Ni, 44.0wt% Ti, 0.04wt% Sn, 0.08wt% Zn, 0.05wt% Ge, 0.01wt% B, 0.03wt% Zr, 0.1wt% Se, 0.07wt% Cu and 0.01wt% Ag. The rest are the same as Example 2.

[0114] Example 10

[0115] Compared with Example 2, the component contents of the nickel-titanium alloy tube body are different, specifically including 55.65wt% Ni, 44.0wt% Ti, 0.04wt% Sn, 0.08wt% Zn, 0.05wt% Ge, 0.01wt% B, 0.03wt% Zr, 0.06wt% Se, 0.07wt% Cu and 0.01wt% Ag. The rest are the same as Example 2.

[0116] Embodiment 11

[0117] Compared with Example 2, the component contents of the nickel-titanium alloy tube body are different, specifically including Ni 55.66wt%, Ti 44.0wt%, Sn 0.04wt%, Zn 0.08wt%, Ge 0.05wt%, B 0.01wt%, Zr 0.03wt%, Se0.05wt%, Cu 0.07wt% and Ag 0.01wt%. The rest are the same as Example 2. Example 12

[0118] Compared with Example 2, the component contents of the nickel-titanium alloy tube body are different, specifically including 55.56wt% Ni, 44.0wt% Ti, 0.04wt% Sn, 0.08wt% Zn, 0.05wt% Ge, 0.01wt% B, 0.03wt% Zr, 0.15wt% Se, 0.07wt% Cu and 0.01wt% Ag. The rest are the same as Example 2.

[0119] Mechanical property tests and corrosion resistance tests were performed on Examples 6 to 12, and all performed well and could meet the medical use requirements. Examples 7, 8, and 10 performed best, followed by Examples 9 and 11, and then Examples 12 and 6. It can be seen that a Zr to Se content ratio of 0.3-0.6, especially 0.45-0.55, is more conducive to building a stable nickel-titanium alloy grain structure, and various properties related to the microstructure are also better.

[0120] Embodiment 13

[0121] Compared with Example 2, the component contents of the nickel-titanium alloy tube body are different, specifically including 56.155wt% Ni, 43.5wt% Ti, 0.03wt% Sn, 0.06wt% Zn, 0.035wt% Ge, 0.01wt% B, 0.05wt% Zr, 0.08wt% Se, 0.05wt% Cu and 0.03wt% Ag. The rest are the same as Example 2.

[0122] Embodiment 14

[0123] Compared with Example 2, the component contents of the nickel-titanium alloy tube body are different, specifically including 56.17wt% Ni, 43.5wt% Ti, 0.03wt% Sn, 0.06wt% Zn, 0.035wt% Ge, 0.015wt% B, 0.03wt% Zr, 0.08wt% Se, 0.05wt% Cu and 0.03wt% Ag. The rest are the same as Example 2.

[0124] The yield strength, tensile strength, elongation, hardness, elastic modulus, fracture strain and corrosion resistance of Example 13 and Example 14 were tested respectively and compared with Example 2. The results showed that Example 13 and Example 14 were obviously inferior to Example 2. It should be that the content ratio of B and Zr or the content sum of B and Zr in Example 13 and Example 14 was not in the optimal range, which was not conducive to better grain refinement, so a good microstructure control result was not obtained, which led to the above-mentioned properties not being optimal.

[0125] Comparative Example 1

[0126] Compared with Example 2, the nickel-titanium alloy tube body includes Ni 56.155wt%, Ti 43.59wt%, Ge 0.035wt%, B 0.02wt%, Zr 0.04wt%, Se 0.08wt%, Cu 0.05wt% and Ag 0.03wt%. The rest is the same as Example 2. That is, compared with Example 2, Sn and Zn, elements for improving biocompatibility and fatigue resistance, are not added.

[0127] After testing: (1) The yield strength of the obtained nickel-titanium alloy tube body is 480MPa, the tensile strength is 710MPa, and the elongation is 11.2%, which are all significantly lower than Example 2. There are obvious cracks and deformations when simulating physiological loading cycles, which cannot meet the use requirements. Obviously, when the elements Sn and Zn are not added, the mechanical properties of the product are significantly reduced. (2) The hardness is 7.4GPa, the elastic modulus is 120GPa, and the fracture strain of the three-point bending test is 1.2%, which are all significantly lower than Example 2. Obviously, the defects in the composition cause the hardness and toughness of the product to fail to meet the use requirements.

[0128] Comparative Example 2

[0129] Compared with Example 2, the nickel-titanium alloy tube body includes Ni 56.155wt%, Ti 43.555wt%, Zn 0.06wt%, Sn 0.03wt%, Zr 0.04wt%, Se 0.08wt%, Cu 0.05wt% and Ag 0.03wt%. The rest is the same as Example 2. That is, compared with Example 2, the strengthening and toughening elements Ge and B are not added.

[0130] After testing: the yield strength of the obtained nickel-titanium alloy tube body is 520MPa, the tensile strength is 732MPa, and the elongation is 13.3%, which are significantly lower than those in Example 2. There are obvious cracks and deformations when simulating physiological loading cycles, which cannot meet the needs of use. Obviously, when the elements Ge and B are not added, it is not conducive to the optimization and control of the microstructure, which leads to unsatisfactory grain size control and poor strength and toughness of the product. Moreover, if Figure 3 As shown: Observing its surface properties, compared with Example 2, the surface of the obtained product is rougher and the glossiness is low and uneven, which shows that failure to optimize and control the microstructure will also affect the surface properties.

[0131] Comparative Example 3

[0132] Compared with Example 2, the nickel-titanium alloy tube body includes Ni 56.155wt%, Ti 43.62wt%, Zn 0.06wt%, Sn 0.03wt%, Ge 0.035wt%, B 0.02wt%, Cu 0.05wt% and Ag 0.03wt%. The rest is the same as Example 2. That is, compared with Example 2, the antioxidant elements Zr and Se are not added.

[0133] After testing: the yield strength of the nickel-titanium alloy tube body is 610MPa, the tensile strength is 865MPa, and the elongation is 19%, which is significantly lower than that of Example 2. There are certain cracks and deformations in the later stage of the simulated physiological loading cycle, which cannot meet the use needs. Obviously, if Zr and Se are not added, oxidation damage may be caused during long-term use due to poor oxidation resistance, which in turn affects the mechanical properties, resulting in a decrease in strength and toughness, and cannot meet the long-term stable mechanical performance requirements.

[0134] Comparative Example 4

[0135] Compared with Example 2, the nickel-titanium alloy tube body includes Ni 56.155wt%, Ti 43.58wt%, Zn 0.06wt%, Sn 0.03wt%, Ge 0.035wt%, B 0.02wt%, Zr 0.04wt% and Se 0.08wt%. The rest is the same as Example 2. That is, compared with Example 2, the antibacterial elements Cu and Ag are not added.

[0136] After testing, the yield strength, tensile strength and elongation of the obtained nickel-titanium alloy tube body are basically the same as those in Example 2. However, there is almost no obvious antibacterial property.

[0137] Comparative Example 5

[0138] Compared with Example 2, after vacuum melting, no graded cooling is performed, and the product is directly cooled to room temperature at a rate of 25°C / min, and then electron beam melting is performed. The rest is the same as Example 2.

[0139] After testing: the yield strength of the obtained nickel-titanium alloy tube body is 534MPa, the tensile strength is 763MPa, and the elongation is 15.5%; the deformation recovery rate at 37°C is 85%, and the deformation recovery rate after 10 cycles of stretching is 82.1%; all of which are significantly lower than Example 2. There are obvious cracks and deformations when simulating physiological loading cycles, which cannot meet the needs of use. Obviously, simply adding Zr and B, which help to refine the grains without graded cooling, is not conducive to microstructure optimization and control, resulting in unsatisfactory grain size control effects, and the strength, toughness and shape memory properties of the product are poor. In addition, the salt spray test shows that the 72h corrosion area is about 8%, and it can be seen that the defects of the microstructure also deteriorate the corrosion resistance of the product.

[0140] Comparative Example 6

[0141] Compared with Example 2, Zr and B are not added to the nickel-titanium alloy tube body, and its composition includes Ni 56.155wt%, Ti 43.56wt%, Zn 0.06wt%, Sn 0.03wt%, Ge0.035wt%, Se 0.08wt%, Cu 0.05wt% and Ag0.03wt%. The rest is the same as Example 2.

[0142] After testing: the yield strength of the obtained nickel-titanium alloy tube body is 513MPa, the tensile strength is 722MPa, and the elongation is 12.8%; the deformation recovery rate at 37°C is 81.2%, and the deformation recovery rate after 10 cycles of stretching is 75.3%; all of which are significantly lower than Example 2. There are obvious cracks and deformations when simulating physiological loading cycles, which cannot meet the needs of use. Obviously, simply performing graded cooling without adding Zr and B that help to refine the grains is also not conducive to microstructure optimization and control, resulting in unsatisfactory grain size control effects, and the strength, toughness and shape memory properties of the product are poor. In addition, the salt spray test shows that the 72h corrosion area is about 10%, and it can be seen that the defects of the microstructure also deteriorate the corrosion resistance of the product.

[0143] Therefore, based on the test results of Example 2, Comparative Example 5 and Comparative Example 6, it can be seen that only by the simultaneous doping of Zr and B and the combined effect of graded cooling can a good microstructure control result be achieved. Without any one of them, although the strength and toughness of the product can be improved to a certain extent, the improvement effect is very limited.

[0144] In summary: The present invention can greatly improve the performance of medical nickel-titanium tubes in chemical composition accuracy, mechanical properties, shape memory properties, corrosion resistance, coating adhesion, hardness and toughness, surface properties and biomedical properties by precisely controlling the composition of nickel-titanium alloy, optimizing the microstructure and strictly following the preparation process. It is expected to provide better material options for vascular stents, orthopedic implants, etc., and promote the development of medical devices towards a safer, more efficient and multifunctional direction.

[0145] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A medical nickel-titanium alloy tube doped with trace amounts of multiple elements, characterized in that: The nickel-titanium alloy tube body comprises 54.5wt%-57.0wt% of Ni and 42.8wt%-45.3wt% of Ti, and the rest are other elements doped in trace amounts; The other elements include: elements for improving biocompatibility and fatigue resistance, strengthening and toughening elements, antioxidant elements and antibacterial elements. The elements for improving biocompatibility and fatigue resistance contain Zn and Sn, the strengthening and toughening elements contain at least one of Ge and B, the antioxidant elements contain Se and Zr, and the antibacterial elements contain at least one of Cu and Ag.

2. The medical nickel-titanium alloy tube doped with trace amounts of multiple elements according to claim 1, characterized in that: The elements for improving biocompatibility and fatigue resistance contain Zn 0.04wt%-0.09wt% and Sn 0.02wt%-0.05wt%, the strengthening and toughening elements contain Ge 0.02wt%-0.05wt% and B 0.01wt%-0.03wt%, the antioxidant elements contain Se 0.05wt%-0.1wt% and Zr 0.03wt%-0.06wt%, and the antibacterial elements contain Cu 0.04wt%-0.07wt% and Ag 0.01wt%-0.04wt%.

3. The medical nickel-titanium alloy tube doped with trace amounts of multiple elements according to claim 2, characterized in that: The content ratio of Sn to Zn is 0.4-0.8, the total content of Ge and B is 0.02wt%-0.06wt%, the content ratio of Zr to Se is 0.3-0.6, and the total content of Cu and Ag is 0.06wt%-0.09wt%.

4. The medical nickel-titanium alloy tube doped with trace amounts of multiple elements according to any one of claims 1 to 3, characterized in that: The total content of B and Zr is 0.05-0.08 and the content ratio of B to Zr is 0.3-0.

6.

5. The medical nickel-titanium alloy tube doped with trace amounts of multiple elements according to claim 1, characterized in that: It also includes a drug release coating disposed on the surface of the nickel-titanium alloy tube body, wherein the drug release layer contains PLGA loaded with antibacterial drugs and / or anti-inflammatory drugs.

6. A method for preparing a medical nickel-titanium alloy tube doped with trace amounts of multiple elements as claimed in any one of claims 1 to 5, characterized in that: The method for preparing the nickel-titanium alloy tube body comprises the following steps: S1, preparing metal particles corresponding to the composition of the nickel-titanium alloy tube body, accurately weighing them after pretreatment, and then mixing them evenly and melting and annealing them to obtain a nickel-titanium rod blank; S2, after the initial processing of the nickel-titanium rod blank, turning it into a nickel-titanium tube blank with an outer diameter of 20-30 mm, and then forming an inner hole with a diameter of 7-9 mm in the middle of the nickel-titanium tube blank by wire cutting; S3, firstly perform hot rolling and primary intermediate annealing treatment in a cycle to process the nickel-titanium tube blank obtained in the previous step to an outer diameter of 4-6 mm, and then perform cold drawing and secondary intermediate annealing treatment in a cycle until the outer diameter is 0.17-0.32 mm; S4. After heat treatment and surface treatment, the finished product is obtained.

7. The preparation method according to claim 6, characterized in that: In step S1, the weighing errors of Ni and Ti are controlled within ±0.02wt% during weighing, and the purity of other elements is ≥99.99% and the weighing errors are controlled within ±0.003wt%; the pretreatment of the metal particles at least includes: cleaning Ni particles to remove surface oil and oxide layer and drying, cleaning Ti particles to remove surface oil and drying, and heat treating Ni particles, Ti particles and other element particles respectively, and accurately weighing Ni particles, Ti particles and other element particles after pretreatment and mixing them evenly; In step S1, the smelting is carried out by combining vacuum induction melting and electron beam melting. After the smelting is completed, the temperature is firstly cooled to 900-1000°C at a rate of 20-30°C / min, and then cooled to room temperature at a rate of 5-10°C / min.

8. The preparation method according to claim 6, characterized in that: In step S3, the conditions for hot rolling and primary intermediate annealing are as follows: hot rolling temperature is 850-950°C, reduction is 30%-50%, primary intermediate annealing temperature is 600-700°C, time is 10-50min and is carried out under inert gas protection.

9. The preparation method according to claim 5, characterized in that: The method further comprises step S5 for forming a drug release coating on the surface of the finished product. Step S5 specifically comprises: firstly coating the surface of the finished product with a drug carrier layer whose active ingredient is PLGA, then immersing the finished product in a solution containing the drug, then taking it out and drying it, coating the surface with chitosan, and finally curing it.

10. The preparation method according to claim 9, characterized in that: The specific operations of step S5 are: Coating the drug carrier layer: spray or spin-coat a chloroform or ethyl acetate solution containing 10wt%-15wt% PLGA and an acetic acid aqueous solution containing 0.5wt%-1wt% chitosan onto the surface of the finished product to form a 5-10 μm thick PLGA-chitosan layer, and vacuum dry; Drug embedding: first prepare the antibacterial and / or anti-inflammatory drugs into an aqueous solution with a concentration of 0.5-2 mg / ml or a hydroalcoholic solution with a water-ethanol volume ratio of 1:1, then immerse the finished product obtained in the previous step in it and keep it for 15-30 minutes, and finally take it out to dry or vacuum dry; Coating control layer: first apply 1-2 μm thick chitosan, then dry; Curing: thermal curing at 50-70°C or cross-linking curing under 365nm UV light.

Citation Information

Cited By

  • Intracranial catheter and catheter assembly

    CN121155000A

  • A catheter and catheter assembly for intracranial use

    CN121155000B